Wellbeing of caregivers of children with disabilities: role of Islamic philanthropy - Abdul Rasool, Mohamed Saladin; Md Jani, Syahrina Hayati; Ahmad, Siti Nurul Akma; Muhd Irpan, Hamidah (2023)
The primary aim of this study is to identify the factors that influences the wellbeing of caregivers of children with disabilities. In addition, to determine how Islamic philanthropy would be able to address this issue. Specifically, this study will identify the role of zakat and waqf in enhancing the wellbeing of caregivers of children with disabilities. This paper involves secondary and primary data sources which are text studies and field studies on certain respondents such as parents/guardians of children with disabilities, related parties with legislation, the party that manages waqf property (Mutawalli) and zakat (MAIN), and the party that provides therapy facilities and Community Rehabilitation Centres (PPDK) by the Department of Welfare and Society (JKM). This study is anticipated to create possibilities for treatment and therapy for caregivers of children with disabilities, thereby fostering a beneficial influence on their child's developmental and potential. Islamic philanthropy has the potential to contribute to the growth of the national economy by alleviating the financial strain on many sectors, including educational institutions, hospitals, and community infrastructure requirements. Islamic philanthropy, particularly through the mechanisms of zakat and waqf, significantly contributes to the improvement of the welfare of caregivers of children with disabilities. Zakat and waqf institutions have the opportunity to develop suitable measures to ensure that caregivers are equipped to effectively care children with disabilities, with the ultimate goal of encouraging their independence as they grow up.